Does eating behaviour among adolescents and young adults seeking obesity treatment differ depending on sex, body composition, and parental country of birth? - Stephanie E Bonn; Anne Christenson; Helén Eke; Linnea Sjöblom; Anna Dahlgren; Ylva Trolle Lagerros (BMC, 2022)
Abstract Background Adolescents and young adults around the world experience high rates of weight gain. The underlying eating behaviours that may lead to overconsumption of energy are complex and can depend on a number of factors. The aim of this study was to explore if eating behaviour among adolescents and young adults referred to specialized obesity treatment differed depending on sex, body composition, and parental country of birth. Methods Adolescents and young adults aged 16-25 years, referred for obesity treatment in 2018-2021 were included in the study. Eating behaviour was assessed using the Three Factor Eating Questionnaire, comprising domains of uncontrolled-, emotional- and cognitive restraint eating. Student's t-test was used to compare differences in eating behaviour scores between males and females, and between those having at least one parent born in a Nordic country and those with both parents born outside the Nordic countries. Associations between BMI, waist circumference, and body fat percentage, and eating behaviour as the dependent variable, were examined using linear regression. Results A total of 463 participants, mean age 21 years and mean BMI 41.3 kg/m2, were included in the analysis. Females scored statistically significantly higher than males on emotional eating (45.8 vs. 35.4, p = 0.002) and cognitive restraint eating (45.4 vs. 39.2, p = 0.009). Participants with at least one parent born in a Nordic country reported a statistically significantly lower score of uncontrolled eating (45.7 vs. 51.3, p = 0.02) compared to participants with both parents born outside the Nordic countries. Further, there were statistically significant inverse associations between cognitive restraint eating scores and BMI (β=-0.64, 95%CI: -0.97 to -0.31), waist circumference (β=-0.44, 95%CI: -0.61 to -0.27) and body fat percentage (β=-0.57, 95%CI: -1.01 to -0.14) in models adjusted for age, sex, smoking, and civil status. Conclusion Our findings suggest that sex and parental country of birth may influence eating behaviours among adolescents and young adults referred for specialist obesity treatment. We also found that cognitive restraint eating decreased with increasing BMI, waist circumference, and body fat percentage. This indicates that there may be an inverse association between the ability to restrain oneself from eating and gaining weight, however, the direction of the association must be investigated further. Increased knowledge about eating behaviours may be valuable in the clinical setting.